Dividual Africa: Nodal Issues of Tradition and Contemporaneity - Kawalec, Anna; Lukaszewicz, Aleksandra (Roczniki Kulturoznawcze, 2023)
The editorial consists of two parts. The first part is an introduction to the complexity of the ‎cultural contexts of the African continent, focusing on this ‎complexity as a specific and important structure of the cultural reality of the world. The ‎second part introduces the issues undertaken by the TPAAE project team, ‎devoted to the traditions and transformations of the Kenyan Coastal ‎Region.‎